2016
DOI: 10.1136/bjophthalmol-2016-308925
|View full text |Cite
|
Sign up to set email alerts
|

Vessel density analysis in patients with retinitis pigmentosa by means of optical coherence tomography angiography

Abstract: This study showed that most of the vascular impairment in patients affected by RP localised in the DCP, with relative sparing of the SCP and CC. DCP alterations were more pronounced outside the hyper-autofluorescent ring on SW-FAF. Vascular impairment may preclude good treatment outcomes in RP patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
104
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(121 citation statements)
references
References 25 publications
12
104
5
Order By: Relevance
“…Furthermore, several studies demonstrated that choroidal thickness is significantly reduced in patients with RP. 34,35 In contrast to our results, Battaglia Parodi et al 16 recently showed no difference in CCP vessel density between RP patients and healthy subjects, which were tested by means of OCTA. Nevertheless, this is probably secondary to the different OCTA types used (Optovue in our study and Topcon in the Battaglia Parodi et al study), or to the different method of analysis (AngioVue software versus ImageJ software), or to different disease stages and genetic features of the groups enrolled (considering there is a poor genetic characterization in both studies).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Furthermore, several studies demonstrated that choroidal thickness is significantly reduced in patients with RP. 34,35 In contrast to our results, Battaglia Parodi et al 16 recently showed no difference in CCP vessel density between RP patients and healthy subjects, which were tested by means of OCTA. Nevertheless, this is probably secondary to the different OCTA types used (Optovue in our study and Topcon in the Battaglia Parodi et al study), or to the different method of analysis (AngioVue software versus ImageJ software), or to different disease stages and genetic features of the groups enrolled (considering there is a poor genetic characterization in both studies).…”
Section: Discussioncontrasting
confidence: 55%
“…15 Battaglia Parodi et al 16 recently showed vascular alterations in RP by means of OCTA. However, they did not evaluate a possible correlation between vascular perfusion and retinal function.…”
mentioning
confidence: 99%
“…For retinal vascular changes, studies suggest that a reduced retinal blood flow could be a response to a decreased metabolism after ganglion cell death and a loss of photoreceptors due to reactive vessel constriction [21-23]. This hypothesis has been supported by the finding of an increase in endothelin-1, a powerful endogenous vasoconstrictor factor in the eyes of retinitis pigmentosa patients [22, 24, 25]. In our study, the postvitelliform group of BVMD revealed a reduction in superficial vessel density compared to the vitelliform group, although the difference did not reach a significant level, possibly due to the limited sample size.…”
Section: Discussionsupporting
confidence: 49%
“…The utility of this technique as an alternative to conventional fluorescein and indocyanine green angiography has been explored for numerous retinal and optic nerve diseases in the past few years with encouraging results 5–14. In addition to qualitative features (eg, subjective assessment of foveal ischaemia), several studies have now reported the use of quantitative measures (eg, retinal capillary plexus density measurements) to evaluate severity and prognosis of conditions such as diabetic retinopathy,15 age-related macular degeneration,16 Stargardt disease17 and retinitis pigmentosa 18…”
Section: Introductionmentioning
confidence: 99%